Modern approaches to the surgical treatment of varicocele in childhood - D.H. Vernihora; V.A. Dihtiar (Zaslavsky O.Yu., 2021)
In the structure of male infertility, varicocele is being detected in 30-40 % cases of primary infertility, and in 80 % cases of secondary infertility. At the age of 10 years during the screening, only 1 % of boys have a varicocele, but in the pubertal period this figure increases to 15-20 %. Indications for surgery in childhood differ from those in adults, since grade III varicocele must be associated with ipsilateral testicular atrophy more than 20 % compared to contralateral, or combined with pain. Surgical methods of varicocele treatment are different. Discussions are ongoing regarding the choice of ligation of the internal spermatic vein. There is no general agreement on the technique of surgical intervention. There are about 100 different methods of internal spermatic vein ligation in the world, the most popular of which are the retroperitoneal approach according to Palomo, transinguinal access according to Ivanissevich, subinguinal ligation according to Marmar, vascular embolization and laparoscopic suprainguinal approach. Currently, there is no gold standard for surgical treatment of varicocele in pediatric surgery in contrast to adulthood, where microsurgical subinguinal varicocelectomy has already become a classic method of intervention. This is due to a lower complication rate compared to high ligation. Subinguinal varicocelectomy can sometimes lead to testicular atrophy due to damage to the testicular artery, which is difficult to visualize during surgery. In childhood, Marmar operation is complicated by the small size of the spermatic cord structures, which requires the search for new methods of intraoperative visualization of vascular structures. In this article, intratesticular injection of 1% methylene blue was used for lymphatic vascular contrast and indirect visualization of the testicular artery, which allows for the use of subinguinal varicocelectomy in adolescents.